2011
DOI: 10.4102/jtscm.v5i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable freight transport in South Africa:Domestic intermodal solutions

Abstract: Due to the rapid deregulation of freight transport in South Africa two decades ago, and low historical investment in rail (with resultant poor service delivery), an integrated alternative to road and rail competition was never developed. High national freight logistics costs, significant road infrastructure challenges and environmental impact concerns of a road-dominated freight transport market have, however, fuelled renewed interest in intermodal transport solutions. In this article, a high-level business ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Primary energy consumption of road freight transport is approximately four times higher than that of rail (Association of American Railroads, 2011). Consequently, in the UK, mainland Europe and the USA the fastest growth of rail freight tonnage is anticipated in the intermodal sectors (Havenga, 2011b;McKinnon, 2009). Other sectors, such as construction and metals, where rail freight originates from industrial premises with rail sidings, are also expected to experience strong growth (McKinnon, 2009).…”
Section: Scenariosmentioning
confidence: 99%
“…Primary energy consumption of road freight transport is approximately four times higher than that of rail (Association of American Railroads, 2011). Consequently, in the UK, mainland Europe and the USA the fastest growth of rail freight tonnage is anticipated in the intermodal sectors (Havenga, 2011b;McKinnon, 2009). Other sectors, such as construction and metals, where rail freight originates from industrial premises with rail sidings, are also expected to experience strong growth (McKinnon, 2009).…”
Section: Scenariosmentioning
confidence: 99%
“…Initial research based on the 2009 data identified 192 million tons (or 100 billion tonkm) of corridor freight (Havenga, Simpson, Fourie, & De Bod, 2011). The research methodology on which these figures were based has since been greatly improved and the 2009 data was updated in conjunction with the 2010 data that was researched based on the same new methodology.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In developed countries logistics and intermodal transportation have become major factors for economic development, spatial communication and market integration. International traffic flows are practically not considered without intermodal technologies, namely, a network of logistics centers and intermodal transport terminals, as stated in studies [4] and [5]. However, to develop such a system, the technical equipment of these terminals and operational procedures should be considered more thoroughly.…”
Section: Literature Review and Statement Of The Problemmentioning
confidence: 99%
“…7, which testify that the following factors influence the probability of a steady state: -according to Fig. 6: 3 Р is the probability of change from truck running gear to rail running gear at the departure station, 5 Р is the probability of change from rail running gear to truck running gear at the destination station, 7 Р is the probability of waiting for rail running gear, 8 Р is the probability of waiting for truck running gear; -according to Fig. 7: 3 Р is the probability of freight transportation by rail to the departure station, 5 Р is the probability of freight delivery with a truck tractor without running gear change by rail to the consignee, 7 Р is the probability of waiting for the truck tractor at the consignor's, 8 Р is the probability of staying in the yard.…”
Section: Formation Of the Bimodal Transportation Procedures By Using Amentioning
confidence: 99%